(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Animal beings’ rights have long been ignored, the main data of legal systems being anthropocentrism that assumes human beings’ superiority. Recently, subjectivity of animals as sentient beings has been gaining acceptance both by science and philosophy, possibly entailing legal subjectivity although most law systems still defend human prerogatives. This paper outlines the evolution of legal provisions and regulations concerning animal beings, both in Italy and in Europe. The Lisbon treaty and its repercussions, and the evolving EU regulations that restrict experimentation on animals are analyzed. Balancing human and animal being interests will be a challenging target for contemporary jourists.